Association between birthweight and hearing loss in older adults. (March 2022) - Gopinath, Bamini; Tran, Yvonne; Tang, Diana; Burlutsky, George; McMahon, Catherine; Mitchell, Paul
Highlights: A U-shaped association between birthweight and hearing loss was found. Both low birthweight and high birthweight were associated with hearing loss. Foetal programming could be involved in the decline of hearing. Abstract: Objectives: We examined the association between birthweight and objectively measured hearing loss in older men and women. Study design: 893 community-dwelling participants aged 50+ years with pure-tone audiometry data and self-reported birthweight were included for cross-sectional analysis. Participants were asked how much they weighed at birth either in pounds and ounces or in kilograms and grams. Main outcome measures: The pure-tone average of frequencies 0.5, 1.0, 2.0 and 4.0 kHz (PTA0.5-4kHz ) >25 dB HL in the better ear established the presence of hearing loss. Results: Around 31.9% and 50.0% of participants who self-reported low (<2.5 kg) and high birthweight (>4.5 kg), respectively, had hearing loss. The odds of experiencing any level of hearing loss (>25 dB HL) after multivariate adjustment was: OR 2.00 (95% CI 1.13-3.56) for low birthweight and OR 2.43 (95% CI 1.23-4.82) for high birthweight, compared with participants in the reference group who self-reported normal birthweight (3.1-4.0 kg). Additionally, participants with high birthweight had 2.4-fold greater odds of having mild hearing loss (25-40 dB HL), while participants with low birthweight had 2.6-fold greater odds of moderate to severe hearing loss. Conclusions: We observed an independent U-shaped association between birthweight and age-related hearing loss, that is, persons born with low or high birthweight had a greater likelihood of experiencing any level of hearing loss in older age. These findings provide further evidence to address an important gap in the literature regarding the influence of foetal growth on the auditory system in later life.